Effects of biochar on availability and plant uptake of heavy metals – A meta-analysis. (15th September 2018) - Chen, De; Liu, Xiaoyu; Bian, Rongjun; Cheng, Kun; Zhang, Xuhui; Zheng, Jufeng; Joseph, Stephen; Crowley, David; Pan, Genxing; Li, Lianqing
Abstract: Biochar can be an effective amendment for immobilizing heavy metals in contaminated soils but has variable effects depending on its chemical and physical properties and those of the treated soil. To investigate the range of biochar's effects on heavy metal accumulation in plants in responses to the variation of soil, biochar and plant, we carried out a meta-analysis of the literature that was published before March 2016. A total of 1298 independent observations were collected from 74 published papers. Results showed that across all studies, biochar addition to soils resulted in average decreases of 38, 39, 25 and 17%, respectively, in the accumulation of Cd, Pb, Cu and Zn in plant tissues. The effect of biochar on heavy metal concentrations in plants varied depending on soil properties, biochar type, plant species, and metal contaminants. The largest decreases in plant heavy metal concentrations occurred in coarse-textured soils amended with biochar. Biochar had a relatively small effect on plant tissue Pb concentrations, but a large effect on plant Cu concentrations when applied to alkaline soils. Plant uptake of Pb, Cu and Zn was less in soils with higher organic carbon contents. Manure-derived biochar was the most effective for reducing Cd and Pb concentrations in plants as compared to biochars derived from other feedstock. Biochar having a high pH and used at high application rates resulted in greater decreases in plant heavy metal uptake. The meta-analysis provides useful guidelines on the range of effects that can be anticipated for different biochar materials in different plant-soil systems. Graphical abstract: Image 1 Highlights: Biochar's efficiency varied with its properties and soil conditions. Biochar was most effective in reducing Cd and Pb uptake by plant. Meta-analysis guides the optimal use of biochar in plant-soil systems.